2007
DOI: 10.2174/157339407780126665
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factors as Targets for Cancer Therapy: AP-1 a Potential Therapeutic Target

Abstract: The field of cancer therapy is rapidly moving forward with the development of numerous prospective new agents designed to inhibit cellular factors involved in signal transduction, cell proliferation, and the onset of apoptosis. At the core of these biological processes are transcription factors that are the functional mediators of these effects. Transcription factors are the downstream targets of numerous signal transduction pathways that are central to the process of carcinogenesis. The Activator Protein-1 (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…Generally, carcinogenesis is considered to have three stages including initiation, promotion, and progression and metastasis. Although mutations of DNA, which can activate oncogenesis or inhibit tumor suppression, were traditionally thought to be crucial factors for the initiation of carcinogenesis, recent studies have demonstrated that other molecular events such as transcription activation, signal transduction, oncogene amplification, and recombination, also constitute significant contributing factors [231, 232]. Studies have shown that mercury and other toxic metals effect cellular organelles and adversely affect their biologic functions [231, 233].…”
Section: Mercurymentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, carcinogenesis is considered to have three stages including initiation, promotion, and progression and metastasis. Although mutations of DNA, which can activate oncogenesis or inhibit tumor suppression, were traditionally thought to be crucial factors for the initiation of carcinogenesis, recent studies have demonstrated that other molecular events such as transcription activation, signal transduction, oncogene amplification, and recombination, also constitute significant contributing factors [231, 232]. Studies have shown that mercury and other toxic metals effect cellular organelles and adversely affect their biologic functions [231, 233].…”
Section: Mercurymentioning
confidence: 99%
“…Although mutations of DNA, which can activate oncogenesis or inhibit tumor suppression, were traditionally thought to be crucial factors for the initiation of carcinogenesis, recent studies have demonstrated that other molecular events such as transcription activation, signal transduction, oncogene amplification, and recombination, also constitute significant contributing factors [231, 232]. Studies have shown that mercury and other toxic metals effect cellular organelles and adversely affect their biologic functions [231, 233]. Accumulating evidence also suggests that ROS play a major role in the mediation of metal-induced cellular responses and carcinogenesis [234236].…”
Section: Mercurymentioning
confidence: 99%
“…84 According to studies conducted by Leaner et al and Zalups et al, Hg has negative effects on cellular organelles and their biological functions. 85,86 There is a controversy surrounding exposure to Hg and carcinogenesis. Some studies have indicated that Hg is genotoxic.…”
Section: à2mentioning
confidence: 99%
“…Taken together, this suggests that AP-1 is a promising target for prevention and therapy in cancer and many other diseases [30].…”
Section: Introductionmentioning
confidence: 89%